To solve this system of equations, let's first write them in standard form:
1) y = x - 1
2) -5x + 2y = -2
Now, we can substitute the expression for y from the first equation into the second equation:
-5x + 2(x - 1) = -2
-5x + 2x - 2 = -2
-3x - 2 = -2
-3x = 0
x = 0
Now that we have found the value of x, we can substitute it back into the first equation to find the value of y:
y = 0 - 1
y = -1
Therefore, the solution to the system of equations is x = 0 and y = -1.
solve the system of equations. y=x-1 -5x+2y=-2
1 answer